2018
DOI: 10.1007/s11904-018-0418-8
|View full text |Cite
|
Sign up to set email alerts
|

Health Behavior Theory to Enhance eHealth Intervention Research in HIV: Rationale and Review

Abstract: Purpose of Review Optimal design and evaluation of eHealth interventions requires the specification of behavioral targets and hypothesized mechanisms of action – both of which can be enhanced with the use of established health behavior theories (HBTs). In this paper, we describe the major HBTs and examine their use in studies of eHealth interventions for HIV prevention and treatment, and assess the contribution of HBT in developing and evaluating eHealth interventions. Recent Finding Based on our review of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 64 publications
1
18
0
1
Order By: Relevance
“…This study’s findings confirm the potential of men’s eHealth programs as previously described in a range of contexts and diverse studies [ 7 , 14 - 25 ]. Adding to the literature focused on understanding men’s eHealth acceptability, engagement, and behavior change, this study contributes some important empirical insights and supports calls for future research to more fully investigate dose-response relationships with randomized controlled trials [ 25 , 26 ]. Although careful not to overstate the current findings or imply attribution, some explanations and potential implications for the statistically significant associations between men’s DCM exposure levels and their recent and intended health behavior changes are offered as a means to scoping adjustments for DCM, and making broader recommendations for the men’s eHealth field.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This study’s findings confirm the potential of men’s eHealth programs as previously described in a range of contexts and diverse studies [ 7 , 14 - 25 ]. Adding to the literature focused on understanding men’s eHealth acceptability, engagement, and behavior change, this study contributes some important empirical insights and supports calls for future research to more fully investigate dose-response relationships with randomized controlled trials [ 25 , 26 ]. Although careful not to overstate the current findings or imply attribution, some explanations and potential implications for the statistically significant associations between men’s DCM exposure levels and their recent and intended health behavior changes are offered as a means to scoping adjustments for DCM, and making broader recommendations for the men’s eHealth field.…”
Section: Discussionmentioning
confidence: 65%
“…Klein et al’s [ 24 ] quasi-experimental, 2-arm study evaluated Real Talk (an eHealth harm reduction intervention targeting black men who have sex with men) reported end user’s HIV knowledge gains (although there were no significant differences between Real Talk and the control participant’s actual condom use or other risk reduction strategies). Although the aforementioned and many other men’s eHealth evaluation studies have been limited by small samples, attrition, and/or a lack of control groups, the results are encouraging [ 25 , 26 ]. In sum, acceptability and evaluation studies confirm the strong potential of men’s eHealth programs amid calls for more evidence to efficiently guide future work and confidently claim sustained health behavior change effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, grounding in theoretical frameworks may also be another indicator of effectiveness, as suggested by the greater uptake of HIV testing reported by theoretically based interventions included in this review. Although the majority of studies in this review reported a theoretical basis for their intervention, the limited number of theory-based, HIV-focused digital interventions have been noted by others [ 85 , 86 ]; this may be attributed to the speed of development and proliferation of digital approaches to improving HIV outcomes. The findings presented here suggest that theoretical grounding is an important component of effective interventions and should be prioritized in future development.…”
Section: Discussionmentioning
confidence: 94%
“…A prior review of health behavior theory and its application to eHealth HIV interventions and research advocated for theory to be incorporated in the design [78], and these findings are relevant for SMS approaches for data collection. While SMS may be used solely as an approach to capture data, it can simultaneously be used to serve as an intervention designed to elicit behavior change.…”
Section: Incorporating Health Behavior Theorymentioning
confidence: 99%